2019
DOI: 10.1055/s-0039-3399572
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Two Locking Plate Constructs for the Stabilization of Feline Tibial Fractures

Abstract: Objectives The aim of this study was to compare the biomechanical characteristics of locking compression plate (LCP) and conical coupling plate (CCP) constructs for the stabilization of experimentally induced gap fractures in cat tibiae. Materials and Methods Pelvic limbs were harvested from eight cat cadavers. Paired tibiae were stripped of all soft tissues, and randomly assigned to the LCP or CCP stabilization group. An eight-hole 2.7 mm LCP or a six-hole 2.5 mm CCP was applied to the medial surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Traditionally, veterinary surgeons have preferentially chosen plate osteosynthesis for feline long bone fracture repair. 9,10 Furthermore, due to potential biomechanical benefits over non-locking designs, locking compression plates (LCP; DePuy Synthes, West Chester, Pennsylvania, USA) have been favoured by many surgeons, 11,12 with the 2.0 and 2.4 mm LCP being routinely selected for feline patients. 11,13 Studies, however, have reported LCP yield failure as a complication, 13,14 presumably resulting from eccentric plate location and subsequent large bending moments in non-reconstructible fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, veterinary surgeons have preferentially chosen plate osteosynthesis for feline long bone fracture repair. 9,10 Furthermore, due to potential biomechanical benefits over non-locking designs, locking compression plates (LCP; DePuy Synthes, West Chester, Pennsylvania, USA) have been favoured by many surgeons, 11,12 with the 2.0 and 2.4 mm LCP being routinely selected for feline patients. 11,13 Studies, however, have reported LCP yield failure as a complication, 13,14 presumably resulting from eccentric plate location and subsequent large bending moments in non-reconstructible fractures.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Our group recently completed a study comparing the biomechanical characteristics of an 8 hole 2.7 mm locking compression plate (LCP) (DePuy Synthes Vet; West Chester, Pennsylvania, United States) to a 6-hole, 2.5-mm CCP and found that LCP constructs were significantly stiffer than the CCP constructs when subjected to both bending and axial loads. 16 In response to the results of that study, the manufacturer developed a prototype CCP (pCCP) to improve the biomechanical profile of the implant (►Fig. 1).…”
Section: Introductionmentioning
confidence: 99%